Pengaruh Penerapan Peraturan Pemerintah pada Pelaksanaan Harga Penjualan Tandan Buah Segar (TBS) Kelapa Sawit di Tingkat Petani Swadaya di Kebun Lingkup Unit Marihat - Arifah Nasution (Universitas Muhammadiyah Enrekang, 2023)
The current problem is the frequent occurance over-supply of fresh fruit bunches of palm oil owned by smallholders that exceed the demand from palm oil processing factories. The purpose of this research isto analyze the realization price of FFB sales at the collecting level, the realization of export sales prices of Crude Palm Oil (CPO), realization of kernel sales prices and government policies on the realization of FFB sales prices at smallholder and the Government policy in the future to increase the bargaining power of farmer of FFB in West Sumatra. Two data sources used are primary and secondary data. Primary data is obtained directly from independent smallholders and other stakeholders, the instruments that researchers use are direct interviews, questionnaires, field observations and focus group discussions. Secondary data used is time series data using the Error Correction Model (ECM) analysis method. The results show that the variable realization price of FFB sales at the Gatherer level, the realization price of export and local CPO sales, the realization of export and local kernel sales prices proved to have a significant effect on the price realization of FFB sales at independent farmers but government policies related to FFB pricing have not significantly affected prices sales realization at the level of independent smallholders. Through the process of monitoring and evaluation of policies that have been established before and determine the right strategy in the future, is one way that can be done by the government to improve the bargaining power farmer of FFB in Unit Marihat